Anthologieserie Systematik und Geschichte eines narrativen Formats - Hauptmann, Kilian; Pabst, Philipp; Schallenberg, Felix (Schriften zur Kultur- und Mediensemiotik, 2022)
Black Mirror, Fargo, True Detective and American Horror Story are among the most discussed serial productions of the last ten years. As different as the series are, they are united by a generic term that has established itself as a self-description in the marketing of the productions and in the reviews of the commentators: anthology series. The aim of the contributions in the anthology is to systematically pursue the anthological in the serial in order to profile the term in the humanities discourse. The contributions ask about the media conditions, such as the connections and differences between collection and series, literary and television series anthologies, as well as the origin and functions of the term. Likewise, specific narrative logics of continuation and closure as well as the resulting moments of coherence of anthology series are examined. This shows that the term is more than clever branding by the production studios. Rather, it represents an operationalizable and analytically resilient category that should be included in the scientific investigation of anthology series.